Studies of corrugated antipodal Vivaldi wideband antenna with notched band and rectenna integration - Nurhayati, Nurhayati; Al Gburi, Ahmed Jamal Abdullah; Setyono, Mohammad Iyo Agus; Anifah, Lilik; Rakhmawati, Lusia; Iskandarianto, Fitri Adi; Ali, Usman (Elsevier Ltd, 2025)
A wideband rectenna based on a Corrugated Antipodal Vivaldi Antenna (AVA) with a notched band is proposed for energy harvesting applications. The antenna performance is studied parametrically by varying the corrugated and rectangular spiral slot (RSS) structures and also by integrating the antenna with a rectenna for energy harvesting applications. The AVA rectenna achieves an S₁₁ of less than -10 dB from 2.38 GHz to beyond 20 GHz. An AVA with two corrugations at the lower position of the radiator increases the bandwidth by 300 MHz compared to an AVA without corrugation. At 2 GHz, AVAs with three and four corrugations exhibit a directivity of 5.73 dBi, compared to 2.9 dBi for an AVA without corrugation. Increasing the corrugation depth enhances the gain, ranging from 3.05 dBi to 9 dBi. The notched band shifts to lower frequencies as the spiral strip slot lengthens, so we can set the desired notched band by adjusting the length and position of the RSS. Furthermore, Integration of a rectangular spiral slot (RSS) enables tunable notched bands, providing flexibility to reject interference from unwanted frequency ranges. The agreement between simulation and measurement confirms that the proposed AVA rectenna is also a strong candidate for wideband energy harvesting applications.